The Search for a European Identity in the Long 1970s: External Relations and Institutional Evolution in the European Community. (9th June 2016) - TULLI, UMBERTO
Abstract : The past decade has seen an explosion of scholarly work on the European Community (EC)'s attempts to develop an international role during the 'long 1970s'. This is hardly surprising: historians tend to follow the opening of the archives, and now is the best moment to examine primary sources from the period. There are, however, two further reasons for this growing interest in European integration during the 1970s. Firstly, writing in the aftermath of the crisis in relations between the United States and Europe provoked by the US's global war on terrorism and at the height of the European financial crisis, many scholars – historians and political scientists alike – have looked back at the crisis of the 1970s, searching for precedents, similarities and differences. Secondly, thanks to the number of studies now available, the decade is widely recognised as a pivotal period of global transformation – a period in which new global dynamics produced radical change for Europe and for the international system as a whole. In many ways, this decade represented a crisis of modernity that saw the emergence of new actors and processes. Cold War categories became too rigid to usefully define – or even explain – an increasingly pluralistic world, in which new international actors, ranging from transnational grassroots movements to international institutions and regular international summits, began to play major roles. The oppressive but unambiguous Cold War order started to crumble, and a new one, characterised by 'interdependence' and 'globalisation', began to emerge. The effects of this transformation were particularly dramatic for Europe: it was in the seventies that Europe 'entered a different world'.